Lack of Activity of Docetaxel in Soft Tissue Sarcomas: Results of a Phase II Study of the Italian Group on Rare Tumors. (1999) - Santoro, Armando; Romanini, Antonella; Rosso, Alberto; Frustaci, Sergio; Comandone, Alessandro; Apice, Gaetano; De Toma, Domenico; Dogliotti, Luigi; Lionetto, Rita; Dani, Carla; Bruzzi, Paolo; Piolini, Marco; et al.
Abstract : Purpose. The prognosis of advanced soft tissue sarcoma is poor, only a few drugs showing some activity with response rates around 15– 25%. Consequently drug development seems mandatory to improve treatment outcome. Following previous favourable EORTC experience, the Italian Group on Rare Tumors started a phase II study with docetaxel to confirm the activity of this drug in soft tissue sarcoma. Patients and methods. Thirty-seven patients with soft tissue sarcoma resistant to at least one anthracyclinecontaining regimen were enrolled in a phase II multicenter study evaluating docetaxel 100 mg/m 2 in a 1-h i.v. infusionq 3 weeks. Results. Thirty-seven patients were enrolled onto this phase II study and 36 were evaluable for response. Only one partial remission was observed [2.8% with 95% confidence interval (CI) 0.1– 16.2%]. Median progression-free and overall survival were 42 and 350 days, respectively. Neutropenia and leukopenia as well as cutaneous manifestations were the most common toxicities. Discussion. The results of this phase II study do not confirm a previous EORTC repor t on the activity of docetaxel in soft tissue sarcoma, but are consistent with other more recent phase II studies. The accumulated evidence does not justify the use of this drug in the management of patients suffering from this disease, resistant to anthracyclinecontaining regimens.